Elaboración de una mascarilla natural a base de pepino (Cucumis sativus) con acción hidratante y suavizante para uso cosmético - Piedra González, Yadira A. (2011)
You use a lot of properly peeled fruit and crushed for their maceration process. For the elaboration of the base gel it uses certain substances of which carries out several rehearsals to obtain the one that present better characteristics according to that settled down.